Analysis of the pesantren environment and leadership style on teacher performance with work-life balance as an intervening variable - Anan Abdul Hanan; Saefulloh Saefulloh; Yoga Fajar Dwi Putra; Dian Wirtadipura; Romli Ardie (Institute of Computer Science (IOCS), 2026)
This study aims to analyze the influence of the pesantren environment and leadership style on teacher performance with Work-Life Balance as an intervening variable. The research used an explanatory quantitative approach and was carried out at the Al-Muawwanah Islamic Boarding School, Ciamis Regency, West Java. The research population includes all active teachers as many as 100 people who are designated as samples through saturated sampling techniques. Data collection was carried out using a Likert scale questionnaire, while data analysis was carried out using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS. The results of the study show that the pesantren environment and leadership style have a positive and significant effect on teacher performance. In addition, the pesantren environment and leadership style also have a significant effect on Work-Life Balance. Work-Life Balance has been proven to have a positive effect on teacher performance and partially mediates the relationship between the pesantren environment and leadership style and teacher performance. These findings affirm the importance of a conducive work environment, supportive leadership, and management of work-life balance as a strategic strategy to improve teacher performance in the pesantren environment